Endoplasmic reticulum stress-mediated glycophagy drives macrophage M1 polarization in silica nanoparticles-induced pulmonary fibrosis - Lei Bao; Zihan Geng; Linpeng Niu; Lili Shi; Liyi He; Yaxian Pang; Cunhui Zhang; Yan Liu; Jiawei Chen; Beibei Shi; Ruiting Wu; Jingyuan Wang; et al. (Journal of Environmental Sciences, 2026)

Seed-associated Pseudomonas enhance the growth of Ambrosia trifida - Xue Chen; Chunying Li; Chang Wang; Jieyu Yang; Ruiting Ju; Fengjuan Zhang; Jihua Wu (Plant and Soil, 2026)

Pan-cancer characterization of the pyrimidine catabolic enzyme UPB1 identifies a tumor-suppressive prognostic biomarker in skin cutaneous melanoma - Yingli Men; Yi Shao; Yongfeng Chen; Ping Wang; Yiyang Li; Zhenzhen Yang; Ruiting Feng; Hui Wang; Yinsen Song; Cong Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Dynamic polysaccharide-based organic nanocomposite hydrogel precisely mediates oral targeted therapy for colorectal cancer - Xinyang Chen; Nuo Li; Huazheng Cheng; Ying Zhang; Ruiting Pan; Qin Shen; Guoqing Yan (Carbohydrate Polymers, 2026)

Short-Chain Fatty Acids Mitigate Perinatal Methylmercury-Induced Cognitive Impairment Via Modulation of the Gut Microbiota Composition - Binqian Han; FangRen Li; Qin Lu; Ruiting Ran; Lianrui Li; Weiying An; Fang Chen; Wenjuan Wang (Biological Trace Element Research, 2026)

Deciphering the impacts of multi-source materials on semi-continuous anaerobic digestion of food waste: performance enhancement and mechanism analysis - Yongdong Chen; Ruiting Zhu; Fang Liu; Xiuxia Zhang; Shi Li; Li Gu; Jiancheng Shu (Journal of Environmental Management, 2026)

High-efficiency two-electron water oxidation tandem system for hydrogen peroxide generation and application - Yonghao Shen; Weiqing Guo; Zhiyong Tu; Qiaozhi Han; Zheshun Ou; Jiating Chen; Ruiting Hu; Zhuofeng Hu (Journal of Environmental Chemical Engineering, 2026)

Repurposing hydrothermal carbonization aqueous product: Leveraging nitrification inhibition to drive a stable assimilatory metabolism for nutrient recovery - Ruiting Zhang; Hong Chen; Jun Sheng; Shiyi Zhao; Xin Yu; Dong Cheng; Hanyue Wu; Xiaoming Zou; Gang Xue (Chemical Engineering Journal, 2026)

Retraction notice to “Construction of functional curdlan hydrogels with bio-inspired polydopamine for synergistic periodontal antibacterial therapeutics” [Carbohydrate Polymers 245 (2020) 116585] - Xianqin Tong; Xiaoliang Qi; Ruiting Mao; Wenhao Pan; Mengying Zhang; Xuan Wu; Gang Chen; Jianliang Shen; Hui Deng; Rongdang Hu (Carbohydrate Polymers, 2026)

The interaction between Ir nanocrystallites and Ni2P nanosheets regulates the adsorption energetics of intermediates for boosting ethanol electrolysis - Xiaoyu Zhang; Ruiting Chen; Ge Ma; Xin Wang; Yu Chen; Zhongwei Chen (Chemical Engineering Journal, 2025)

Activity-related exposure to outdoor air pollution: A spatiotemporal inquiry of residents in Beijing, China - Ruiting Gao; Lanlan Qi; Chen Lu (Environmental Research, 2025)

Manganese ore tailings packed electrochemical precipitation wall: A novel approach of phosphorus removal and mechanistic insights - Shaoqin Chen; Ruiting Zhu; Jiancheng Shu; Lu Li; Buxiao Kuang (Journal of Environmental Management, 2025)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

Carbon black induced pulmonary fibrosis through piR-713551/PIWIL4 targeting THBS2 signal pathway - Mengruo Wang; Yong Niu; Qingping Liu; Peihao Yang; Mengqi Wu; Ruiting Wu; Beibei Shi; Jiawei Chen; Jingyuan Wang; Zhe Du; Yaxian Pang; Lei Bao; et al. (Journal of Environmental Sciences, 2025)

Vacancy engineering in transition metal selenides for long-lasting and fast-charging Na-ion batteries - Changsheng An; Jialing Liu; Chen Xu; Chi Zhang; Ruiting Li; Shumin Zhang; Shiying Zhang; Jinbo Li; Chao Cai; Xing Ou (Chemical Engineering Journal, 2025)

Freshness Prediction of Silver Carp Using Sub-Layer Equivalent Circuit Parameters in Electrochemical Impedance Spectroscopy - Jian Sun; Ruiting Xia; Feng Lin; Kai Wu; Jinfu Chen; Gangshan Wu; Wei Pan; Tingting Zou (Journal of Aquatic Food Product Technology, 2025)

Three-dimensional ordered macroporous nitrogen-doped carbon for efficient adsorption of flavonoids from plant extraction - Chuanmao Li; Wenyuan Lyu; Ruiting Lin; Haoran Liu; Yingfei Wang; Datong Chen; Fengliang Wang; Yingwei Li (Chemical Engineering Journal, 2025)

Sulfur cycle, a new opportunity for nitrogen removal from textile wastewater: A review - Shiyi Zhao; Hong Chen; Jun Sheng; Xin Yu; Kejia Zeng; Dong Cheng; Hanyue Wu; Ruiting Zhang; Xianbao Xu; Xiaoming Zou; Gang Xue (Journal of Water Process Engineering, 2024)

Room temperature oxygenated groups addition in carbon materials via ozone oxidation for boosting electrochemical H2O2 production - Jinchao Xu; Wanying Wang; Yuang Shi; Huan Li; Ruiting Hao; Gang Chen; Wen Wang; Chunning Zhao; Weichao Wang (Chemical Engineering Journal, 2024)

Layered deposited MoS2 nanosheets on acorn leaf like CdS as an efficient anti-photocorrosion photocatalyst for hydrogen production - Yao Wang; Tengyang Gao; Ruiting Li; Yan Chen; Wen Luo; Yang Wu; Yu Xie; Yong Wang; Yifan Zhang (Fuel, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Correlation analysis and predicting modeling of pyrolysis gas based on landfill excavated waste pyrolysis characteristics - Yufeng Du; Ruiting Liu; Ping Han; Jin Wang; Feiyong Chen; Guanzhong Chen (Chemosphere, 2024)

Unraveling the generation mechanism of singlet oxygen in Bi2WxMo1-xO6 solid solution and roles in photocatalytic degradation of gaseous toluene under visible-light irradiation - Shaobo Cao; Lei Wu; Jun Li; Yang Li; Kang Da; Wenting Chen; Ruiting Xue; Jian Yang; Ximei Fan (Journal of Environmental Chemical Engineering, 2024)

Transcription profiles and phenotype reveal global response of Staphylococcus aureus exposed to ultrasound and ultraviolet stressors - Yun Bai; Yuanhang Zhou; Ruiting Chang; Xueli Hu; Yingying Zhou; Jiabo Chen; Zhi Zhang; Juanjuan Yao (Science of The Total Environment, 2024)

Individual and interactive effects of air warming and elevated O3 on carbon fixation and allocation in two urban tree species - Yijing Wang; Sheng Xu; Bo Li; Yan Li; Ruiting Wang; Wei Chen; Xingyuan He; Felicity Hayes; Maihe Li (Agricultural and Forest Meteorology, 2024)

Investigating synergism and mechanism during sequential inactivation of Staphylococcus aureus with ultrasound followed by UV/peracetic acid - Yun Bai; Yuanhang Zhou; Ruiting Chang; Yingying Zhou; Xueli Hu; Jiawei Hu; Chuanyao Yang; Jiabo Chen; Zhi Zhang; Juanjuan Yao (Journal of Hazardous Materials, 2024)

An attomolar-level electrochemical DNA biosensor based on target-triggered and entropy-driven catalytic amplification integrated with AuNPs@ZIF-8 nanocomposites for oral cancer overexpressed 1 detection - Jing Li; Qi Jiang; Minhui Chen; Wei Zhang; Ruiting Liu; Jin Huang; Qin Xu (Analytica Chimica Acta, 2024)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Nebulization Therapy with Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes for COVID-19 Pneumonia - Meiping Chu; Hao Wang; Linjie Bian; Jiehui Huang; Danping Wu; Ruiting Zhang; Fangli Fei; Yigang Chen; Jiazeng Xia (Stem Cell Reviews and Reports, 2022)
Background Scientists have been facing numerous challenges in the development of an effective therapeutic strategy for the treatment of COVID-19 pneumonia. Several studies have suggested that improving patient immunity and reducing lung injury induced by SARS-CoV-2 may be effective for treating patients with COVID-19. Methods A pilot trial of nebulization therapy with exosomes of mesenchymal stem cells (MSCs) was performed on seven patients with COVID-19 pneumonia. Exosomes secreted from MSCs were collected and purified using multiple ultrafiltration steps. All patients were treated with nebulization of MSC-derived exosomes, and primary safety and efficacy outcomes were evaluated. Results Our clinical study demonstrated that nebulization of MSC-derived exosomes is a novel method that might be utilized in the treatment of COVID-19 pneumonia. Nebulization of MSC-derived exosomes did not induce acute allergic or secondary allergic reactions but did promote the absorption of pulmonary lesions and reduce the duration of hospitalization for mild cases of COVID-19 pneumonia. Conclusions Nebulization of MSC-derived exosomes is a safe, effective, and simple method, and their application at the beginning of treatment may be more beneficial. Trial Registration Chinese Clinical Trial Registry, ChiCTR2000030261. Registered on 26 February 2020. Graphical Abstract

ALIX increases protein content and protective function of iPSC-derived exosomes - Ruiting Sun; Yingying Liu; Meng Lu; Qianqian Ding; Pingping Wang; Heng Zhang; Xiaoyu Tian; Peng Lu; Dan Meng; Ning Sun; Meng Xiang; Sifeng Chen (Journal of Molecular Medicine, 2019)